Ruby & Olivia - Hawkins, Rachel, 1979- (G.P. Putnam's Sons, 2017)
Quiet Olivia and brash Ruby, her twin sister's best friend, paired at a summer camp for troublemakers to work in an old mansion, must really unite when strange things begin to happen.